1981
DOI: 10.1104/pp.67.4.849
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Stimulated Fusion of Different Plant Cell Protoplasts

Abstract: Cell fusion is induced between guard cell and mesophyll cell protoplasts of Vicia faba by electrical field application. The process of fusion is initiated by electrical breakdown of the cell membrane. Prior to the application of an external electrical field pulse which brings about reversible breakdown of the membrane, the cels (suspended in a low-conducting medium) are brought into close contact with one another by exposing them to an external alternating, nonuniform field (5 volts, electrode distance, 200 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…fusion between stomatal protoplasts and mesophyll protoplasts of V. faba) is also reported in the literature [59,69,86,87]. We can thus conclude that this technique works efficiently as far as the fusion of plant protoplasts is concerned.…”
Section: Plant Protoplasts and Vacuolessupporting
confidence: 70%
“…fusion between stomatal protoplasts and mesophyll protoplasts of V. faba) is also reported in the literature [59,69,86,87]. We can thus conclude that this technique works efficiently as far as the fusion of plant protoplasts is concerned.…”
Section: Plant Protoplasts and Vacuolessupporting
confidence: 70%
“…We have demonstrated that N. crassa slime cells can be subjected to dielectrophoresis and electrofusion under conditions comparable to those applied to other plant protoplasts [10]. Both processes are related to the electric properties of cell membranes, and, according to our expectations, all 3 slime mutants responded equally to external electric fields.…”
Section: Discussionsupporting
confidence: 56%
“…Two types of wave form of the pore ptilse exist. The initial wave form used by Zimmermann and Scheurich (1981) is a square ptilse and is the wave form that is used most. The benefits of using sqtiare pulses are that the exact parameters for pore formation, that is, external field strength and pulse length, can be determined precisely.…”
Section: Electrofusion Generatorsmentioning
confidence: 99%